BE THE BEST OF THE BEST - LIM YEN RUEN - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
PENANG, 20 April 2017 A Universiti Sains Malaysia (USM) alumnus, Lim Yen Ruen has made the university proud when he received The Institute of Engineers Malaysia (IEM) Gold Medal Award at the IEM 58th Annual Dinner & Awards Night 2017, held at the One World Hotel in Petaling Jaya, recently.